Cranial Ultrasound and MRI in Preterm Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Cranial ultrasound (cUS) and conventional MRI, performed on the same day at term age, were compared in a population-based cohort of 72 extremely low gestational age (ELGA) infants (below 27 weeks) in a study at the Karolinska Institute, Stockholm, Sweden; and Sophia Children's Hospital, Rotterdam, The Netherlands.